Islamic Theology in Muslim Chinese Writings: Qingzhen Shiyi of Jin Tianzhu as an Example; Teologi Islam dalam Karya-Karya Cina Islam: Qingzhen Shiyi karya hasil Jin Tianzhu sebagai salah satu contoh - Zhan ming, Ma (Journal of Islam in Asia (E-ISSN 2289-8077), 2011)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> <!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> Abstract Qingzhen Shiyi is an Islamic theology work in Chinese language authored by an eighteenth century Chinese Muslim scholar known as Jin Tianzhu. The main reason for writing this book was twofold: (2) removing suspicion from the then Chinese government officials' minds that Muslms' behavior was against the Chinese culture and practices, and (2) letting Chinese Muslims know the original teachings of Islam concerning their daily lives. This work appears to be theological cum jurisprudential because the author has discussed Islamic practices from these two angles. His arguments are to some extent apologetic because to justify the efficacy of Islamic rites and rituals the author has brought the views of Confucius. He has also been logical to explain why certain Muslim practices were highly appreciable. This paper aims at introducing that Chinese Muslim scholar and his work Qingzhen Shiyi, focusing mainly on Tianzhu's theological views on God, reward and punishment etc. and legal views on lawful and unlawful, celebration of Eid festival, charity work, wearing skullcap, ritual bath etc.